2001
DOI: 10.1515/jpem.2001.14.1.85
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Weight Loss on Fibrinolytic and Metabolic Parameters in Obese Children and Adolescents

Abstract: We studied i) whether short-term weight loss alters plasminogen activator inhibitor-1 antigen (PAI-1-Ag) and tissue-type plasminogen activator antigen (tPA-Ag) in obese children, and ii) whether changes in body composition and/or abdominal adiposity are responsible for changes in PAI-1 and tPA-Ag. 20 obese boys (mean age 11.9 yr) and 40 obese girls (mean age 12 yr) were studied before and after three weeks of low-caloric diet and physical activity. Body composition was assessed by means of bioelectrical impeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Hispanic adults with impaired glucose tolerance and diabetes have increased levels of PAI-1, which are associated with BMI, fasting insulin, and proinsulin and are negatively associated with the ISI (33). This strong association between PAI-1 levels and obesity and insulin resistance has also been identified in children and adolescents (34,35). Accordingly, our data show that both PAI-1 and t-PA levels are strongly associated with BMI and truncal fat in Hispanic youth as well as with hs-CRP.…”
Section: Multivariate Analysismentioning
confidence: 82%
“…Hispanic adults with impaired glucose tolerance and diabetes have increased levels of PAI-1, which are associated with BMI, fasting insulin, and proinsulin and are negatively associated with the ISI (33). This strong association between PAI-1 levels and obesity and insulin resistance has also been identified in children and adolescents (34,35). Accordingly, our data show that both PAI-1 and t-PA levels are strongly associated with BMI and truncal fat in Hispanic youth as well as with hs-CRP.…”
Section: Multivariate Analysismentioning
confidence: 82%
“…Several trials have demonstrated improvements in insulin sensitivity following exercise intervention programmes [33][34][35][36][37][38][39][40][41] and, moreover, that cessation of activity reverses the training-induced changes. 37 However, in one trial involving 10 weeks of exercise training in 24 obese black girls, no significant change in fasting insulin was observed but this may be explained by compensatory behaviour, since only self-reported vigorous physical activity and not overall volume of activity was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies in children have demonstrated the utility of increased physical activity to improve metabolic regulation after 3 weeks of daily exercise and low calorie diet (38) and to reduce BP after 8 months following three additional physical education lessons per week (39). Four months of training (5 ϫ 40 min/ week) resulted in significant decreases in insulin, triglycerides, and body fat but no changes in glucose and HDL cholesterol in 79 obese children (40).…”
Section: Conclusion -The Relationshipmentioning
confidence: 99%